1992
DOI: 10.1083/jcb.118.5.1071
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of insoluble secretory product from bovine thyroid: extracellular storage of thyroglobulin in covalently cross-linked form.

Abstract: Abstract. ExtraceUular storage of thyroglobulin (TG)is an important prerequisite for maintaining constant levels of thyroid hormones in vertebrates. Storage of large amounts is made possible by compactation of TG in the follicle lumen with concentrations of at least 100-400 mg/ml. We recently observed that the luminal content from bovine thyroids can be isolated in an intact state and be separated from soluble TG. For this purpose, bovine thyroid tissue was homogenized and subjected to various steps of purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Human Tg globules consist of Tg mainly cross-linked by disulfide bridges (4,5). In addition to disulfide cross-links, isodipeptide bonds were detected in bovine (3,6), and dityrosine links in porcine Tg globules (31). Here, we have observed the occurrence of multilayered Tg in mouse thyroids, indicating that covalently cross-linked Tg exists also in the lumen of mouse thyroid follicles (Figure 8).…”
Section: Solubilization Of Luminal Tg Depends On Expression Of Cathepsupporting
confidence: 50%
“…Human Tg globules consist of Tg mainly cross-linked by disulfide bridges (4,5). In addition to disulfide cross-links, isodipeptide bonds were detected in bovine (3,6), and dityrosine links in porcine Tg globules (31). Here, we have observed the occurrence of multilayered Tg in mouse thyroids, indicating that covalently cross-linked Tg exists also in the lumen of mouse thyroid follicles (Figure 8).…”
Section: Solubilization Of Luminal Tg Depends On Expression Of Cathepsupporting
confidence: 50%
“…It is worth noting that a similar absence of coimmunoprecipitating Tg, PDI, and BiP has been shown previously (25). Nevertheless, because the fate of Tg exported from the cultivated thyrocytes is quite different from the situation in the thyroid gland where secreted Tg is stored in the follicular lumen in form of compact, cross-linked aggregates (36), one cannot exclude the existence of the extracellular ERp29/Tg complexes in vivo.…”
Section: Erp29 a Novel Thyroglobulin Folding/secretion Factormentioning
confidence: 65%
“…Covalent cross-links between Tg molecules has been suggested as a way to store Tg at a high concentration without increasing the osmolality (4,5). The present study shows that globules are mostly observed in follicles with a low Tg turnover, 'hypofunctioning' follicles in the normal human thyroid and 'cold' follicles in aged mice.…”
Section: Discussionmentioning
confidence: 49%
“…It has been suggested that Tg compaction is a mechanism to store the prohormone at high concentration (4,5). A morphological heterogeneity in the colloid aspect along with the presence of intrafollicular globules has also been observed on fixed histological sections (7,8).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation